Legal Regulation in Digital Medicine - OSADCHUK, M.A.; OSADCHUK, A.M.; KIREEVA, N.V.; TRUSHIN, M.V. (Journal of Advanced Research in Law and Economics; Vol 11 No 1 (2020): JARLE Volume XI Issue 1(47) Spring 2020DO - 10.14505//jarle.v11.1(47).18, 2020)
The civilized world has achieved enormous progress in digital medicine, which is becoming the basis for further healthcare development. In the near future this can significantly improve people`s life , increase budget efficiency in the sphere of health, improve health indicators and life expectancy of the next generation. In this situation, digital medicine does not fully guarantee exclusion of any data leakage risks. This means that the use of better technologies in health care will require stricter compliance with a complex network of existing laws and regulations, which vary depending on the country, jurisdiction and region (for example, the European Union).However, this global process implementation requires strong political will to protect citizens from confidential data misuse, to increase responsibility of manufacturers and consumers of digital equipment and technologies to their citizens and the state.